Nonmonotonic Dose–Response Curves Occur in Dose Ranges That Are Relevant to Regulatory Decision-Making. Issue 3 (11th September 2018) - Hill, Corinne E.; Myers, J. P.; Vandenberg, Laura N.
Non-monotonic dose response curves (NMDRCs) occur in cells, tissues, animals and human populations in response to nutrients, vitamins, pharmacological compounds, hormones and endocrine disrupting chemicals (EDCs). Yet, regulatory agencies have argued that NMDRCs are not common, are not found for adverse outcomes, and are not relevant for regulation of EDCs. Under the linear dose response model, high dose testing is used to extrapolate to lower doses that are anticipated to be 'safe' for human exposures. NMDRCs that occur below the toxicological no-observed-adverse-effect level (NOAEL) would falsify a fundamental assumption, that high dose hazards can be used to predict low dose safety. In this commentary, we provide examples of NMDRCs and discuss how their presence in different portions of the dose response curve might affect regulatory decisions. We provide evidence that NMDRCs do occur below the NOAEL dose, and even below the 'safe' reference dose, for chemicals such as resveratrol, permethrin, chlorothalonil, and phthalates such as DEHP. We also briefly discuss the recent CLARITY-BPA study, which reported mammary adenocarcinomas only in rats exposed to the lowest BPA dose. We conclude our commentary with suggestions for how NMDRCs should be acknowledged and utilized to improve regulatory toxicity testing and in the calculation of reference doses that are public health protective.